2022
DOI: 10.1186/s12884-022-05012-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of unexplained persistent sinus tachycardia in women with structurally normal heart during the peripartum period

Abstract: Background Persistent sinus tachycardia (ST) is frequently encountered during pregnancy and peripartum period and its etiology often remains elusive. We sought to examine the possible association between unexplained persistent ST and obstetric outcomes. Methods A case control study was conducted using chart review of women admitted in labor to one of 7 hospitals of Northwell Health between January 2015 to June 2021. After excluding women with struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Specifically, Varrias et al showed that sinus tachycardia is mainly considered physiologic in pregnancy but is associated with unfavorable outcomes. 98 In the Dipep study, pregnant and postpartum women were tested for PE. Those without PE exhibited similar rates of typical PE symptoms, including pleuritic chest pain (52%), shortness of breath (54%), palpitations (13%), cough (8%), and syncope (5%) relative to women with validated, proving that solely clinical diagnosis of PE in pregnant population is a diagnostic conundrum.…”
Section: Challenges In Physical Examinationmentioning
confidence: 99%
“…Specifically, Varrias et al showed that sinus tachycardia is mainly considered physiologic in pregnancy but is associated with unfavorable outcomes. 98 In the Dipep study, pregnant and postpartum women were tested for PE. Those without PE exhibited similar rates of typical PE symptoms, including pleuritic chest pain (52%), shortness of breath (54%), palpitations (13%), cough (8%), and syncope (5%) relative to women with validated, proving that solely clinical diagnosis of PE in pregnant population is a diagnostic conundrum.…”
Section: Challenges In Physical Examinationmentioning
confidence: 99%